English lesson material of reservationist professions in handling personal hotel rooms through telephone - Ni Luh Putu Sri Widhiastuty; I Made Wardhana (Politeknik Negeri Bali, 2018)
Reservationist / reservation officer of Front Office Hotel is in charge of handling hotel room reservations. The duty of the hotel's front-line reservationist is to record and complete tasks related to hotel room orders, filing room reservation data, control room inventory well, calculate forecasting, make arrival list guests (arrival list) based on existing bookings, create group information lists, create VIP information lists, create room occupancy statistics, and create daily, monthly, and yearly reports. One ability to apply good selling techniques namely the ability of a reservationist to communicate with foreign guests using the English language. English is the language of international communication, which is needed by employees who work in the world of tourism and hotels in Bali, especially for hotel front reservationist. A hotel front desk reservationist is required to communicate using the correct and standard English when serving guests who make hotel reservations. Reservationists who accept hotel room bookings by phone, usually start the conversation using the standard greeting. As a reservationist, the understanding of hotel products should really be considered, such as the location of the rooms, the types of rooms available, the applicable room rates and other service facilities available at the hotel.